Evaluation of community perceptions on outdoor air pollution in Marapong and Onverwacht Townships, Lephalale Local Municipality, South Africa - Mabeba, Motsoka Refiloe Audrey (My University, 2024)
Outdoor air pollution is a challenge globally, especially in developing countries. It is associated with deleterious effects on the environment and human health. The aim of this study is to evaluate how the communities of Marapong and Onverwacht perceive outdoor air pollution and the risks they are exposed to. It is conducted to identify whether the respondents are relating outdoor air pollution to particular diseases and environmental issues, as well as how they perceive the measures implemented to tackle outdoor air pollution and its related effects. The study area is located in Lephalale Local Municipality. For this study, primary data and secondary data were collected. The primary data was collected using questionnaires distributed to 232 participants from the two townships of Lephalale Local Municipality. Questionnaires were used to collect data to assess how communities perceived outdoor air pollution and its effects. Existing literature from secondary data sources such as the internet, government publications, articles and journals were also used to collect and extract information on outdoor air pollution in global, regional and local countries as well as its associated human health and environmental implications. The study findings revealed that participants from both Marapong and Onverwacht townships are aware of the occurrence of outdoor air pollution in their localities and the impact it has on their health as well as their surrounding environment. However, the participants had limited knowledge of measures implemented by the private and public sectors to address the challenges of outdoor air pollution and its associated environmental and human health implications. The study concludes that residents in the affected areas lack awareness and are not adequately involved in decision-making processes to address outdoor air pollution and implement control measures. Therefore, it recommends raising awareness in the communities both public and private sectors about the sources, consequences, and mitigation measures of outdoor air pollution through various information sources. This includes encouraging individuals to take action to minimize the generation of outdoor air pollution. Understanding how people are impacted, their concerns, priorities, and willingness to accept governmental policies or laws is essential for developing effective measures to address the issue of outdoor air pollution.
Thesis (M. Sc. (Geography)) -- University of Limpopo, 2023
Keywords: Perception; Outdoor air pollution; Communities; Awareness; Risks; Air -- Pollution -- South Africa -- Limpopo; Air -- Pollution -- Measurement